EFFECT OF HEAT STRESS AND NUTRITION STATUS ON WORKER FATIGUE AT TRADITIONAL MUSIC GAMELAN INDUSTRY - Lusi Ismayenti (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Industry of gamelanproduction is informal industry from motherhood heritage of Java. Making gamelan worker direct heat exposure and consume large man power, thus need good physic stamina especially in heatting process. Aims: This study aim to know the effect of heating stress and nutrition status on worker fatique. Method: This study conducted by observation, quesionare, documentation and measurement. Respondents were 30 gamelan-producing workers at forging process dan finising process from 105 populationwithpurposive sampling in Wirunvillage Sukoharjo Central Java Indonesia.Measurement of heating stress using area heat stress tool. Status of nutrition was measured by body weight eighing, while the fatique was measuded by timer reaction tool. Statistic analysis with linear regression. Results: Results showed that heating stress in forging process part has Wet Bulb Globe Temperature(WBGT) average 31oC (>threshold value) and and at finishing process part has WBGT average 27,9 oC (≤threshold value), that means in heatting process was more fatigue compared to in finishing process. Linear regression statistical test with p-value 0.008 (≤0,05) showed there is effect of heat stress on worker fatigue.There was relationship between nutrition status and work fatique, where worker with good status of nutrition have no fatique of 6.67 %, low fatique of 50%, and medium fatigue of 6.67 %. All of worker with low status of nutrition getting fatigue, whereas worker with excessive nutrition status also getting fatigue by medium fatigue of 20 % and high fatigue of 6.67%. Linear regression statistical test with p-value 0.04 (≤0,05) showed there is effect of nutrition status on worker fatigue. Conclusion: Workers in forging site more likely to experience work fatigue than workers in finisshing site. There is effect of heat stress on worker fatigue. There is significant association between nutritional status and work fatigue.